Advances and Innovations in Educational Network Infrastructure: A Systematic Review - Cantuarias, Luis; Gomez, Javier; Zarate-Perez, Eliseo (LACCEI, 2024)
The purpose of this systematic review is to identify innovations for educational network infrastructure in institutions, avoiding vulnerabilities to improve scalability among different devices. The PRISMA method was used for the selection of studies, from which 107 articles were obtained from the Scopus database. After applying the eligibility criteria, 73 articles were excluded, leaving only 34 articles included for their respective analysis. The results show that technologies such as cloud computing, blockchain, the Internet of Things (IoT), and mixed reality can improve educational network infrastructure by providing greater speed, bandwidth, scalability, and security. However, significant investment is required for their implementation. It is concluded that a solid and updated network infrastructure is essential to leverage the benefits of new technologies in education, enhancing pedagogical innovation and improving educational quality; however, its implementation would involve addressing technical, economic, organizational, and teaching challenges.